2018
DOI: 10.1016/j.bbabio.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ferredoxin to algal photosystem I involves a single binding site and is composed of two thermodynamically distinct events

Abstract: Despite the impressive progress made in recent years in understanding the early steps in charge separation within the photosynthetic reaction centers, our knowledge of how ferredoxin (Fd) interacts with the acceptor side of photosystem I (PSI) is not as well developed. Fd accepts electrons after transiently docking to a binding site on the acceptor side of PSI. However, the exact location, as well as the stoichiometry, of this binding have been a matter of debate for more than two decades. Here, using Isotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…It is well documented that steady H 2 production can take place as long as the CBB cycle is inhibited [24, 55]. Such inhibition, if constant, is expected to manifest in a reduced growth rate due to the inhibition of carbon fixation [56]. Furthermore, a diminished CBB cycle will eventually result in overreduction of the plastoquinone pool and acidification of the lumen [57, 58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that steady H 2 production can take place as long as the CBB cycle is inhibited [24, 55]. Such inhibition, if constant, is expected to manifest in a reduced growth rate due to the inhibition of carbon fixation [56]. Furthermore, a diminished CBB cycle will eventually result in overreduction of the plastoquinone pool and acidification of the lumen [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we were able to obtain some evidence indicating a direct binding of the fusion protein to PSI; however, decisive proof could not be obtained. For example, while studying the interaction using quartz crystal microbalance and dissipation [62] did support this notion, a classical isothermal titration calorimetry [56] and pull-down assays (Additional file 1: Figure S2) could not verify these findings. In this regard, it was already suggested that PSI binding could improve H 2 production in C. reinhardtii using the Fd–Hyd fusion protein [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reinhardtii strains with His6-tag added to the N-terminus of the PsaA protein (PBC1 pKR152 for WT and PBC1 pKR411 for the strain bearing a mutation in codon 689 of psaA exon 3 (psaA-3)) were grown in TAP medium at 25 °C with constant air flow under continuous white light (~70 µmol photons m −2 s −1 ). The culture was harvested, and thylakoid membranes and mature PSI complexes were purified as described in (28). The fraction corresponding to the mature PSI complexes was collected, concentrated, and stored at −80 °C.…”
Section: Strains Growth Thylakoid Membrane and Psi Isolationmentioning
confidence: 99%
“…The recombinant C. reinhardtii Pc, Fd and ferredoxin-NADP + oxidoreductase (FNR) were heterologously expressed in Escherichia coli BL21 cells, and purified as described in (28) and (29).…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%